2014
DOI: 10.1097/01.tp.0000438206.04348.b2
|View full text |Cite
|
Sign up to set email alerts
|

Donor Quality of Life up to Two Years After Living Donor Liver Transplantation

Abstract: One and two years after donation, QOL is not substantially impaired in the majority of donors. Future research needs to provide an even longer prospective follow-up and should more rigorously explore risk factors for a negative donor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…13,14,[33][34][35][36][37][38][39][40][41] The SF-36 is the most frequently used tool for measurement of HRQoL, and the scores are comparable to the findings in our present study. [34][35][36][37]40,41 Compared with the HRQoL shown in the general population, liver donors had equal scores in most examinations. 35,37,41 However, some studies found decreased physical and psychologic scores postoperatively.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…13,14,[33][34][35][36][37][38][39][40][41] The SF-36 is the most frequently used tool for measurement of HRQoL, and the scores are comparable to the findings in our present study. [34][35][36][37]40,41 Compared with the HRQoL shown in the general population, liver donors had equal scores in most examinations. 35,37,41 However, some studies found decreased physical and psychologic scores postoperatively.…”
Section: Discussionsupporting
confidence: 80%
“…[34][35][36][37]40,41 Compared with the HRQoL shown in the general population, liver donors had equal scores in most examinations. 35,37,41 However, some studies found decreased physical and psychologic scores postoperatively. 33 The physical aspects of HRQoL appear to be especially decreased in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the elevated rates of these problems are reported in the same literature—and sometimes within the same study—that also reports that liver donors’ generic HRQOL meets or exceeds that of the general population. 6,12,20,27,28 This suggests that generic measures may be insensitive for living donors and should be used primarily as adjuncts to more sensitive, specific assessment of donors’ potential problems. 6,12,29,30 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, expanding the donor pool and reducing waiting list mortality is one of the major challenges today for the liver transplant community. 4 Increasing the frequency of living donor liver transplantations (LDLT) meets both of those challenges 5,6 This article collates online resources related to LDLT with relevance to the readership of Transplantation.…”
mentioning
confidence: 99%